Pemikiran Manajemen Pendidikan Pesantren Nurcholis Majid - Toha Ma'sum; M. Munir (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
Pesantren is an Islamic educational institution that has a very large share for the religion of Islam and character formation for the Indonesian nation. Pesantren which is currently very surviving makes a major contribution in the journey of the nation, with its traditional functions brought by muslim scholar Zamakhsyari Dhofier with the tradition of pesantren, and the role of Kyai, but also pesantren requires the renewal of systems directed at community development. Therefore, nurcholish madjid as a reform figure provides ideas to revise or update pesantren education management systems in managing existing resources so as to achieve success. The results of this study show that pesantren education management manages and organizes human resource education institutions to achieve goals efficiently and effectively through managerial functions. The management of pesantren education according to Nurcholish Madjid is a modern and traditional management of pesantren education management by producing superior human resources efficiently and effectively through managerial functions. The other side is that pesantren management is an activity in organizing and managing pesantren education through managerial functions.